An Algorithm for the Diagnosis of Behcet Disease Uveitis in Adults - AKMAN, MEHMET (TAYLOR & FRANCIS INC, 2022)
Purpose: To develop an algorithm for the diagnosis of Behcet's disease (BD) uveitis based on ocular findings. Methods: Following an initial survey among uveitis experts, we collected multi-center retrospective data on 211 patients with BD uveitis and 207 patients with other uveitides, and identified ocular findings with a high diagnostic odds ratio (DOR). Subsequently, we collected multi-center prospective data on 127 patients with BD uveitis and 322 controls and developed a diagnostic algorithm using Classification and Regression Tree (CART) analysis and expert opinion. Results: We identified 10 items with DOR >5. The items that provided the highest accuracy in CART analysis included superficial retinal infiltrate, signs of occlusive retinal vasculitis, and diffuse retinal capillary leakage as well as the absence of granulomatous anterior uveitis or choroiditis in patients with vitritis. Conclusion: This study provides a diagnostic tree for BD uveitis that needs to be validated in future studies.
Keywords: Behcet disease; uveitis; diagnosis; classification criteria; classification and regression tree (CART) analysis; INDOCYANINE GREEN ANGIOGRAPHY; OPTICAL COHERENCE TOMOGRAPHY; CHOROIDAL THICKNESS; CLASSIFICATION; FLUORESCEIN; CRITERIA